ANALISIS KODE ETIK PROFESI AKUNTAN PUBLIK: PERSPEKTIF AL-HADITS - Sugandi, Sugandi; Sulhani, Sulhani (I-Economics, 2024)
A financial report audited by public accountants carries significant responsibility as the basis for decision-making for stakeholders and serves as a symbol of the reliability of financial information for an entity. However, several cases of ethics and regulatory violations have occurred in some prominent KAP in Indonesia. This phenomenon underscores the importance of enforcing ethical codes for the public accounting profession. This research aims to analyze the ethical code of the public accounting profession based on the perspective of Islamic teachings contained in Al-Hadiths. Employing a qualitative descriptive method and an interpretative approach, data were gathered from various sources, including hadiths, scholarly journals, and existing codes of ethics for public accountants. The findings depict that Islamic ethics emphasize good behavior in daily interactions, grounded in principles such as justice, ihsan, honesty, responsibility, and diligence. These principles serve as guidelines for public accountants to perform their duties with integrity, responsibility, high levels of honesty, and ensuring the accuracy of financial information in line with Islamic principles. Furthermore, the code of ethics for public accountants in the Islamic perspective emphasizes principles of integrity, objectivity, competence, professional care, confidentiality, and professional behavior. The implications of this research underscore the importance of understanding and applying Islamic ethical principles in accounting practices to achieve professionalism aligned with religious teachings. Thus, this research is expected to provide valuable contributions to enriching understanding of the relationship between Islamic ethics and accounting practices and promoting the adoption of practices in harmony with the moral values of the hadiths.